A dual‐continua framework for assessing water use models and the potential for conservation. (22nd December 2015) - Prince Czarnecki, Joby M.; Omer, Austin R.; Kröger, Robert
Abstract : Regions vary in their supply of and access to ground and surface waters. These two issues together have substantial influence on the pressures and drivers of water conservation adoption (i.e., necessity vs voluntary adoption). A framework for water use models is proposed where regions are evaluated on two continua, infrastructure (engineered and political) and freshwater supply (physical and usable). Eight illustrative regions are placed into four quadrants based on water‐related infrastructure and supply. Regions in quadrant I experience both ample water supply and adequate infrastructure to still be operating with conservation as a 'luxury.' Regions falling within quadrants II and IV experience a shortage of either supply (II) or infrastructure (IV) but adequate levels of the opposite factor. Regions falling within quadrant III bear the double burden of limited supply and infrastructure. Shifts in quadrants are examined as a function of movement along infrastructure and supply axes. This study seeks to answer (1) for a region with both ample supply and sufficient access to freshwater, what are the mechanisms by which the situation will degrade; (2) for regions lacking either supply or infrastructure (or both) what are the mechanisms by which the situation can be improved; and (3) how do regions maintain status in preferred quadrants? WIREs Water 2016, 3:235–250. doi: 10.1002/wat2.1131 This article is categorized under: Engineering Water > Planning Water